IMMUNOHISTOCHEMICAL CHANGES IN TISSUE OF LUNG AND PERIBRONCHIAL LYMPH NODES DURING PNEUMONIA ARISEN ON THE BACKGROUND OF СHRONIC HEART FAILURE - Павлова О. О. (World of Medicine and Biology, 2015)
With the help of immunohistochemical methods research of lung tissue with pneumonia that associated with CHF it is established: during serous - purulent type of inflammation was observed deficiency of collagen types III and I, while serous - desquamative - lack of type IV, immune response characterized by macrophage and B-cell activation, T-cell inhibition, activation of IgM, IgA and IgG, IL-1 and inhibition - IL-6 producers. In the lymph node tissue was reduced number of cells expressing receptors for CD56, and increase the number of cells producers of IgM, IgG, IgA, IL-1, IL-6, indicating the presence of dissociation syndrome, which is a companion secondary immunodeficiency.